Adult Congenital Heart Disease in Pregnancy. Issue 6 (June 2015) - Lindley, Kathryn J.; Conner, Shayna N.; Cahill, Alison G.
<x xml:space="preserve">Abstract</x> With the success of modern surgical techniques for congenital heart disease, the population of women of childbearing age with congenital heart disease is growing. Because of the significant hemodynamic load of pregnancy, labor, and delivery, women with congenital heart disease require preconceptual risk assessment and expert multidisciplinary care throughout pregnancy. The aim of this review is to discuss the management of cardiovascular, obstetric, and fetal care issues that are commonly encountered during pregnancy in women with congenital heart disease. Target Audience Obstetricians gynecologists, family physicians Learning Objectives After completing this activity, the learner will be better able to discuss the importance of preconceptual risk assessment of pregnancy risk for women with adult congenital heart disease; identify disease-specific complications associated with pregnancy in women with adult congenital heart disease; identify common fetal risks associated with pregnancy in women with adult congenital heart disease; and explain the importance of delivery planning in women with adult congenital heart disease.